The prevalence and clinical relevance of 2R/2R TYMS genotype in patients with gastrointestinal malignancies treated with fluoropyrimidine-based chemotherapy regimens - Khushman, Moh’d (Pharmacogenomics J, 2021)
INTRODUCTION: The prevalence of 2R/2R TYMS genotype is variable but estimated to be around 20–30% in Caucasians. The clinical relevance of TYMS 2R/2R genotype in predicting severe fluoropyrimidine-related adverse events (FrAE) is controversial. Here, we explored the prevalence and clinical relevance of 2R/2R TYMS genotype. METHODS: Between 2011 and 2018, 126 patients were genotyped for TYMS. FrAEs were graded according to CTCAE version 5.0. Fisher’s exact test was used for statistical analysis. RESULTS: The prevalence of TYMS 2R/2R genotype was 24.6%. Among patients with TYMS genotypes (N = 71) that predict decreased TS expression, 2R/2R TYMS genotype was the most common TYMS genotype seen in female (57%) and African American (60%) patients. Among patients with genotypes that predict increased TS expression (N = 55), 12 patients had grade 3–4 FrAEs (22%), while among patients with genotypes that predict decreased TS expression (N = 71), 30 patients had grade 3–4 FrAEs (42%) (p = 0.0219). Compared to patients with genotypes predicting increased TS expression, 17 out of 31 patients (55%) with TYMS 2R/2R genotype had grade 3–4 FrAEs (p = 0.0039) and 15 out 40 patients (38%) with TYMS 2R/3RC and TYMS 3RC/3RC genotype had grade 3–4 FrAEs (p = 0.1108). CONCLUSION: The prevalence of TYMS 2R/2R genotype was 24.6%, and it had a unique sex and ethnic distribution. Polymorphism in the promoter region of TYMS gene that predicts decreased TS expression due to 2R/2R variant was associated with grade 3–4 FrAEs. These data suggest that genotyping patients who are not DPD deficient for TYMS might identify patients at risk of severe FrAEs.